The Use of Bioactive Glass as a Bone Graft Substitute - Öztopalan, Dicle Fırat; Durmuş, Ali Said (Dicle Üniversitesi, 2017)
Autogenous, allogeneic bone graft materials and alloplastic materials has been used in the repair of bone defects since the past. Although most commonly used bone grafts are autogenous grafts, they have significant disadvantages. These disadvantages can be listed as the lack of graft source, the pain that the donor site has taken, nerve injury, infection and regional deformations. Allogeneic bone grafts have got very important complications as disease transfer and graft rejection. The absence of bone banks in the field of veterinary medicine also limits the use of allografts. Therefore, materials that replace bone grafts are being used today increasingly. Bioceramics are the important biomaterials that can be used as bone substitute, especially when autogenous grafts are inadequate. In this review, the properties of bioactive glass and the results of bioactive glass applications to accelerate bone healing were evaluated.

Kemik defektlerinin onarımında otojen, allojen kemik greft materyalleri ve alloplastik materyaller geçmişten günümüze kullanılmıştır. En yaygın kullanılan kemik greftleri otojen greftler olmasına rağmen önemli dezavantajları bulunmaktadır. Bu dezavantajlar greft kaynağının azlığı, alındığı sahada oluşturduğu ağrı, sinir yaralanması, enfeksiyon ve bölgesel deformasyonlar olarak sayılabilir. Allojen kemik greftleri ise hastalık transferi ve rejeksiyon riski gibi önemli komplikasyonları bulunmaktadır. Veteriner hekimlik alanında kemik bankalarının bulunmaması allogreft kullanımını ayrıca sınırlandırmaktadır. Bu nedenle kemik grefti yerine geçen materyaller günümüzde giderek artan bir şekilde kullanılmaktadır. Biyoseramikler, özellikle otojen greftler yetersiz olduğunda, kemik yerine kullanılabilecek önemli biyomalzemelerdir. Bu derlemede biyoaktif camın özellikleri ve kemik iyileşmesi hızlandırmak amacıyla gerçekleştirilen biyoaktif cam uygulamalarının sonuçları değerlendirildi.
Kemik Grefti Yerine Biyoaktif Cam Kullanımı
Keywords: Veterinary Surgery; Veteriner Cerrahi